Variation in the immune responses against Plasmodium falciparum merozoite surface protein-1 and apical membrane antigen-1 in children residing in the different epidemiological strata of malaria in Cameroon - Kwenti, Tebit Emmanuel (Malar J, 2017)
BACKGROUND: Studies to assess the immune responses against malaria in Cameroonian children are limited. The purpose of this study was to assess the immune responses against Plasmodium falciparum merozoite surface protein-1 (MSP-1(19)) and apical membrane antigen-1 (AMA-1) in children residing in the different epidemiological strata of malaria in Cameroon. METHODS: In a cross-sectional survey performed between April and July 2015, 602 children between 2 and 15 years (mean ± SD = 5.7 ± 3.7), comprising 319 (53%) males were enrolled from five epidemiological strata of malaria in Cameroon including: the sudano-sahelian (SS) strata, the high inland plateau (HIP) strata, the south Cameroonian equatorial forest (SCEF) strata, the high western plateau (HWP) strata, and the coastal (C) strata. The children were screened for clinical malaria (defined by malaria parasitaemia ≥ 5000 parasites/µl plus axillary temperature ≥ 37.5 °C). Their antibody responses were measured against P. falciparum MSP-1(19) and AMA-1 vaccine candidate antigens using standard ELISA technique. RESULTS: A majority of the participants were IgG responders 72.1% (95% CI 68.3–75.6). The proportion of responders was higher in females (p = 0.002) and in children aged 10 years and above (p = 0.005). The proportion of responders was highest in Limbe (C strata) and lowest in Ngaoundere (HIP strata) (p < 0.0001). Similarly, the mean IgG antibody levels were higher in children aged 10 years and above (p < 0.0001) and in Limbe (p = 0.001). The IgG antibody levels against AMA-1 were higher in females (p = 0.028), meanwhile no gender disparity was observed with MSP-1. Furthermore the risk of clinical malaria (p < 0.0001) and the mean parasite density (p = 0.035) were higher in IgG non-responders. CONCLUSION: A high proportion of IgG responders was observed in this study, suggesting a high degree exposure of the target population to malaria parasites. The immune responses varied considerably across the different strata: the highest levels observed in the C strata and the lowest in the HIP strata. Furthermore, malaria transmission in Cameroon could be categorized into two major groups based on the serological reaction of the children: the southern (comprising C and SCEF strata) and northern (comprising HWP, HIP and SS strata) groups. These findings may have significant implications in the design of future trials for evaluating malaria vaccine candidates in Cameroon.